Overwintering of the boreal butterfly Colias palaeno in central Europe - Vrba, P; Dolek, M; Nedved, O; Zahradnickova, H; Cerrato, C; Konvicka, M (Cryo letters, 2014)
BACKGROUND: Colias palaeno (Linnaeus, 1761) (Lepidoptera: Pieridae) is a butterfly with boreal distribution with declining populations in peat bogs and subalpine habitats in Central Europe. OBJECTIVE: We investigated the cold tolerance of overwintering caterpillars from one mountain population from Czech Republic (960m a.s.l.) and one alpine population from Italy (2000m a.s.l.). METHODS: We measured supercooling point (SCP), lower lethal temperature (LLT) and content of cryoprotectants. RESULTS: The caterpillars were freeze-avoiding, with lower LLT close to their very low SCP (-25 to -27 degree C). The mountain population accumulated high concentrations of glycerol (5% fresh mass) and sugars (trehalose 0.8%, glucose 0.2%), while the Italian alpine population only moderate amounts of glycerol (0.3%) and sugars (trehalose 0.5%, glucose 0.3%) without effect on their cold hardiness. Larvae that overwintered at +5 degree C had a lower body mass than those overwintering in natural conditions, indicating a metabolic weight loss, but both groups survived equally well. CONCLUSION: We hypothesize that the high concentration of glycerol contributes to the high desiccation tolerance.
Keywords: larva; Freezing; kryoprotektivní látky; Glucose; Larva; Europe; zvířata; Cryoprotective Agents; Glycerol; glukosa; Cold Temperature; ekosystém; trehalosa; nízká teplota; Ecosystem; Evropa; Acclimatization; motýli; Animals; zmrazování; Trehalose; aklimatizace; glycerol; Butterflies